2021
DOI: 10.1177/01945998211012300
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic Membrane Perforation After Intratympanic Steroid Injection: A Systematic Review and Meta‐analysis

Abstract: Objective We investigated the incidence of tympanic membrane (TM) perforations induced after intratympanic steroid injection (ITSI) in patients with sudden sensorineural hearing loss (SSNHL) through a systematic review and meta-analysis. Data Sources PubMed, Embase, and MEDLINE. Review Methods Primary database searches were performed, and 1901 records were identified. After removal of 1802 articles through abstract screening, the remaining 99 full-text journals were assessed for eligibility to be included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…In our series, persistent TM perforation was found in 5% (1 of 20) of the patients after treatment, which is similar to the rate reported in the literature for local application of steroids through ventilation tube. The meta-analysis by Kim et al (24) showed that the proportion of TM perforation after ITS was 7.3% in the ventilation tubing group. Robey et al (25) reported a much higher risk of TM perforation after placement of transtympanic Silverstein microwick for steroid administration, with 29% (48 of 166) of patients having a permanent perforation.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, persistent TM perforation was found in 5% (1 of 20) of the patients after treatment, which is similar to the rate reported in the literature for local application of steroids through ventilation tube. The meta-analysis by Kim et al (24) showed that the proportion of TM perforation after ITS was 7.3% in the ventilation tubing group. Robey et al (25) reported a much higher risk of TM perforation after placement of transtympanic Silverstein microwick for steroid administration, with 29% (48 of 166) of patients having a permanent perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various attempts to treat tinnitus, ITDI is clinically burdensome in that it is slightly invasive. Complications such as hearing loss, eardrum perforation, and middle ear inflammation are known to be rare after ITDI [ 22 ], but clinicians feel these complications to be more difficult than those after ITDI used to treat other diseases (such as sudden sensorineural hearing loss or Menière disease). In this study, we evaluated the effectiveness of ITDI for tinnitus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque no existe acuerdo en el tipo de corticoide, concentración, número de inyecciones, forma y frecuencia de aplicación [6, 12], el Consenso Español del año 2019 [5] al igual que otros [1, 6], aconseja una inyección transtimpánica semanal de dexametasona 8mg/ml, durante 3 semanas. El riesgo principal es la perforación timpánica [34].…”
Section: Materials Y Métodounclassified